Seroconversion Is Misleading as a Test for HSV-2 Infection in Prophylactic Genital Herpes Vaccine Trials: Results of Vaccine Studies in Guinea Pigs - Valerie Bromberg; Lauren M. Hook; John M. Lubinski; Zauraiz Syeda; Kevin P. Egan; Gary H. Cohen; Sita Awasthi; Harvey M. Friedman (Viruses)
Seroconversion is defined as a four-fold or greater rise in antibody titers. This assay is used in human prophylactic vaccine trials to confirm HSV as the cause of genital lesions and detect subclinical latent infection. We evaluated the accuracy of seroconversion in detecting infection using a guinea pig model of genital infection. Not all animals intravaginally inoculated with HSV-2 become infected, particularly if vaccinated; therefore, we need to establish criteria to determine whether an animal is infected. Our primary analysis involved considering animals to be infected if they had any of the following: (a) genital lesions; (b) HSV-2 DNA in vaginal secretions four or more weeks after HSV-2 inoculation as a marker of reactivation from latency; or (c) HSV-2 DNA in dorsal root ganglia, the site of latency. In the second analysis, we considered animals to be infected if they had positive virus cultures from vaginal swabs obtained on day two or four post HSV-2 inoculation. In the third analysis, we considered animals to be infected if they had any condition included in the first two analyses. We collected sera prior to HSV-2 inoculation and two months later and tested the first 57 animals for seroconversion using Western blotting and gG2 IgG ELISA. The results were concordant in 54 of 57 animals (95%), and when discordant, the gG2 ELISA matched infection results as defined by the primary analysis. The remaining animals were evaluated by gG2 IgG ELISA only. A total of 43 animals were inoculated with HSV-2 but not vaccinated (No vaccine group), and 224 were vaccinated with glycoprotein or mRNA vaccines prior to HSV-2 inoculation (Vaccine group). In the No vaccine group, we detected no false positives (seroconversion without infection) but 24% to 29% false negatives (no seroconversion despite infection) depending on the criteria used to define infection. In the Vaccine group, we detected 8% to 22% false positives and 31% to 37% false negatives. The accuracy of seroconversion was 74% to 79% in the No vaccine group and 71% to 76% in the Vaccine group. These results raise concerns about using seroconversion as a diagnostic test in human vaccine trials. Alternate approaches, such as subject home swabbing for HSV DNA, should be considered as a possible replacement.